Innovative Research on the Internationalization Pathways of Brand Communication in the Digital Era - Liu, Yixuan (International Journal of Global Economics and Management, 2024)
In the digital era, the importance of international brand communication is gaining prominence, with digital marketing emerging as a fundamental tool that plays a critical role in global dissemination. Despite extensive academic discussions on the theoretical foundations and strategies of digital marketing within brand communication, there exists a research gap pertaining to the effective dissemination of brands through digital marketing across diverse cultures and markets, particularly in terms of specific practical pathways on social media platforms. This paper aims to enhance theoretical research by providing brand managers with a framework of international communication strategies rooted in digital marketing, aimed at assisting brands in gaining a competitive edge in the global marketplace.